2018
DOI: 10.1039/c7dt04785a
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional (time, wavelength and intensity) functioning fluorescent probe for the selective recognition/discrimination of Cu2+, Hg2+, Fe3+ and F ions

Abstract: We have strategically incorporated three different fluorophores at tren to construct a multi-energy donor/acceptor "smart" probe L. This probe operates by using three-dimensional scales (response time, wavelength and fluorescence intensity) which allows for the selective recognition and discrimination of the Cu, Hg, Fe and F ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The observed ratiometric absorption changes revealed that sensor L can behave as a ratiometric sensor for Ca 2+ . It is recognized that ratiometric responsive probes are superior to other types of probe given their built-in correction for environmental effects and self-correcting capability . On the other hand, the fluorescence titration experiments revealed a fluorescent quenching phenomenon upon increasing the amount of Ca 2+ (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The observed ratiometric absorption changes revealed that sensor L can behave as a ratiometric sensor for Ca 2+ . It is recognized that ratiometric responsive probes are superior to other types of probe given their built-in correction for environmental effects and self-correcting capability . On the other hand, the fluorescence titration experiments revealed a fluorescent quenching phenomenon upon increasing the amount of Ca 2+ (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The detection limit of probe TRN for Zn 2+ , Cu 2+ , Al 3+ and Hg 2+ was calculated based on the fluorescence titration data according to a reported method [47] . Under optimal conditions, calibration graphs for the determination of Zn 2+ , Cu 2+ , Al 3+ and Hg 2+ were constructed.…”
Section: 1mentioning
confidence: 99%
“…The association constants are estimated to be 1.88 × 10 4 M -1 ( TRN• Zn 2+ ), 2.73 × 10 4 M -1 ( TRN• Zn 2+ •Cu 2+ ), and 1.54 × 10 4 M -1 ( TRN •Hg 2+ ) by using a Benesi-Hildebrand plot assuming a 1:1 stoichiometry, respectively ( Fig.S5~S7). The association constants of T RN• Al 3+ are estimated to be 8.60 × 10 8 M -2 by using a Benesi-Hildebrand plot assuming a 1:2 stoichiometry ( Fig.S8)[46] .From the fluorescence titration, a linear relationship between the emission intensity of TRN and ions concentration was observed ( Fig.S9 ~ S13).The detection limit of probe TRN for Zn 2+ , Cu 2+ , Al 3+ and Hg 2+ was calculated based on the fluorescence titration data according to a reported method[47] . Under optimal conditions, calibration graphs for the determination of Zn 2+ , Cu 2+ , Al 3+ and Hg 2+ were constructed.…”
mentioning
confidence: 99%
“…Thanks to the facile preparation and numerous possibilities for the functionalization of compound 1, there are many possible avenues to explore. 11,16 In view of the high importance of anion recognition and the interesting properties of azobenzene compounds, 17 we have introduced the (E)-2-hydroxy-5-((4-nitrophenyl)diazenyl)benzaldehyde group to compound 1 and constructed a tripodal structure. Schiff base groups can be unstable for certain applications, so.…”
Section: Synthesismentioning
confidence: 99%
“…Compound 1 was prepared by following the reported procedures. 11,16 UV-Vis absorption spectra were conducted on a UV-1800 spectrophotometer (Shimadzu) in a 1 cm quartz cell. 1 H and 13 C NMR spectra were measured on a JEOL JNM-ECZ400S 400 MHz NMR spectrometer (JEOL) at room temperature using TMS as an internal standard.…”
Section: Materials and Equipmentmentioning
confidence: 99%